PENGARUH KOMBINASI PUPUK KOMPOS TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETASTANAMAN BAWANG MERAH (Allium ascalonicum L). - Rudiyanto, Rudiyanto; Faqih, Achmad; Nur, Subandi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2022)
This experiment aims to determine the effect of the combination of compost fertilizer on the growth and yield of three varieties of shallot (Allium ascalonicum L). The experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The time of the study was carried out from July to November 2021. The location is located at an altitude of 493 meters above sea level (asl), the soil type is Latosol and Regosol association, including type C rain (slightly wet). The experimental method used is the experimental method with a combination randomized block design (RAK), the treatment consists of two factors, repeated three times. The first factor is compost, which consists of three levels, namely compost 10 tons/ha, compost 15 tons/ha, and compost 20 tons/ha. While the second factor is the variety which consists of three levels, namely the pancasona variety, violetta variety, and the bima variety. The main observation data were processed using linear model statistical tests, analysis of variance, and Scott-knot cluster further test analysis. To determine the correlation between the treatment and the growth and yield components of the shallots, the correlation used is the product-moment correlation coefficient. The experimental results showed: (1) The combination of compost fertilizer and shallot plant varieties affected the weight of fresh bulbs per plot and weight of dry bulbs per clump, but had no effect on plant height, number of leaves, number of tillers per clump, root volume, number of tubers per plant, tuber diameter per plant, fresh tuber weight per plant, and dry tuber weight per plot, (2) The highest dry tuber weight per plot was produced by a combination of compost fertilizer treatment of 10 tons/ha and Bima variety of 3.85 kg/plot or equivalent to 10,26 tons/ha and not significantly different from other treatment combinations, and (3) There was a significant correlation between plant height and number of leaves aged 35 DAP and 45 DAP with seed weight per plot in weak and medium categories. However, there was no significant correlation between plant height and number of leaves at 25 DAP with seed weight per plot with a very weak category.